AN APPROACH OF ENGLISH TEACHING FOR AUTOMOTIVE AND VEHICLE ENGINEERING STUDENTS - Purnama Ayu; Wahyuningsih Usadiati; Elanneri Karani (Intensive Journal, 2021)
English for Specific Purposes (ESP) is generally interpreted as an approach to learning English based on the goals/needs of the learner. In the context of learning English in Indonesia, both at secondary and tertiary schools, especially for automotive students, the ESP approach is a popular choice. The application of this approach is in line with the government policy in the field of education which emphasizes the purpose of learning English, namely to improve the ability of students to use English, especially for academic and professional career needs with an emphasis on reading skills that allow students to understand authentic material topics according to their majors. effectively. This article puts forward a theoretical study of the basic concepts of ESP including its definition and role as a learning approach, along with related issues including needs analysis as the main feature of ESP, syllabus, learning objectives, materials, methodology, and evaluation of ESP-based English learning.